2018
DOI: 10.1017/s0033291717003877
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cannabis potency and first-time admissions to drug treatment: a 16-year study in the Netherlands

Abstract: Background. The number of people entering specialist drug treatment for cannabis problems has increased considerably in recent years. The reasons for this are unclear, but rising cannabis potency could be a contributing factor. Methods. Cannabis potency data were obtained from an ongoing monitoring programme in the Netherlands. We analysed concentrations of δ-9-tetrahydrocannabinol (THC) from the most popular variety of domestic herbal cannabis sold in each retail outlet (2000)(2001)(2002)(2003)(2004)(2005)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 35 publications
2
75
1
2
Order By: Relevance
“…THC has been positively associated with harms in several studies using a range of experimental and observational research methods [2][3][4][5][6]10]. THC has been positively associated with harms in several studies using a range of experimental and observational research methods [2][3][4][5][6]10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THC has been positively associated with harms in several studies using a range of experimental and observational research methods [2][3][4][5][6]10]. THC has been positively associated with harms in several studies using a range of experimental and observational research methods [2][3][4][5][6]10].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that products with higher THC concentrations carry a greater risk of harm. First, several [2][3][4][5][6] (but not all [7]) observational studies have found associations between the potency of cannabis products and problems related to addiction and mental health. Secondly, naturalistic studies indicate that cannabis users only partially adapt their smoking behaviour to variation in potency, resulting in higher doses of THC when using more potent products [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In states with legal marijuana markets (such as Washington), average THC levels for cannabis extracts have been found to be more than three times those for cannabis flowers (Smart et al, 2017). Frequent use of high-potency marijuana has been associated with dependence severity (Freeman and Winstock, 2015), and increases in potency have been linked with increases in first-time admissions to drug treatment for problems associated with cannabis (Freeman et al, 2018). It may be that one factor influencing higher prevalence of frequent marijuana use by age 30 for individuals in the more recent cohorts is higher potency and associated higher levels of dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, consumption of today’s marijuana exposes users to much higher levels of THC than in the past. A study from the Netherlands found that THC concentrations in cannabis products sold at retail outlets from 2000 to 2015 had roughly doubled from 2000 to 2015 [11]. New products on the market are even higher in THC: cannabis extracts (used for “dabbing”) have more than triple the THC content of the buds or other plant parts commonly used for smoking (68.7 vs. 20.6%) [12].…”
Section: Resultsmentioning
confidence: 99%